2002
DOI: 10.17221/4367-pse
|View full text |Cite
|
Sign up to set email alerts
|

Identification of sex in F1 progenies of hop (Humulus lupulus L.) by molecular marker

Abstract: Sex identification for hop (Humulus lupulus L.), which is a dioecious plant, is very important for breeding process. The use of molecular methods for marker-assisted selection (MAS) provides rapid and reliable identification of sex in F 1 progenies. In the first, we proved the use of specific PCR molecular marker for evaluation of sex in selected plants. This marker was not amplified in 3 from 35 male plants. In the next, we successfully analysed 770 genotypes of F 1 progenies of three crossings. The amplified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 16 publications
1
15
0
Order By: Relevance
“…However, the use of these markers has had mixed success in breeding, as the majority remain unverified across second or multiple populations. For some of these markers there is also evidence for incomplete linkage to the male sex [33]. The best described male sex-linked marker is a microsatellite, HLAGA7, being completely linked to the male sex in two Slovenian populations and on a representative sample of male hop genotypes [22].…”
Section: Introductionmentioning
confidence: 99%
“…However, the use of these markers has had mixed success in breeding, as the majority remain unverified across second or multiple populations. For some of these markers there is also evidence for incomplete linkage to the male sex [33]. The best described male sex-linked marker is a microsatellite, HLAGA7, being completely linked to the male sex in two Slovenian populations and on a representative sample of male hop genotypes [22].…”
Section: Introductionmentioning
confidence: 99%
“…6 were the first to publish a sex-specific DNA sequence in hop, developed from random amplified polymorphic DNA (RAPD) molecular markers by using bulk segregant analysis (BSA), which is predominantly present on the Y chromosome and hybridized only weakly to female DNA. Upon testing 5,23 , this first sex-linked marker did not appear to coincide completely with the phenotypic assessments. Jakše et al .…”
Section: Discussionmentioning
confidence: 89%
“…Progress in hop breeding is limited by the biology of hop. Hop can take up to two years under field conditions to reach reproductive maturity 5,6 . Furthermore, as the female hop cones are the commercial product it is difficult to relate the commercial requirements with the male phenotype since cones do not develop on male plants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likely, the few cases of plants with unexpected sex are the result of incomplete linkage between the genetic marker and actual sex determination gene of the plant. High but not complete linkage of the Polley et al (1997) marker with sex was also reported by Patzak et al (2002). The incompleteness of sex identification markers (see also Danilova & Karlov, 2006) might be due to sex chromosome distortions and influence from autosomes on sex determination.…”
mentioning
confidence: 90%